A Role for Exosomes in Craniofacial Tissue Engineering and Regeneration - Cooper, Lyndon F.; Ravindran, Sriram; Huang, Chun-Chieh; Kang, Miya (Frontiers in Physiology, 2020)
Tissue engineering and regenerative medicine utilize mesenchymal stem cells (MSC) and their secretome in efforts to create or induce functional tissue replacement. Exosomes are specific extracellular vesicles secreted by MSCs and other cells that carry informative cargo from the MSC to targeted cells that influence fundamental cellular processes including apoptosis, proliferation, migration, and lineage-specific differentiation. In this report, we review the current knowledge regarding MSC exosome biogenesis, cargo and function. This review summarizes the use of MSC exosomes to control or induce bone, cartilage, dentin, mucosa, and pulp tissue formation. The next-step engineering of exosomes provides additional avenues to enhance oral and craniofacial tissue engineering and regeneration.